Selection of suitable wavelengths for estimating total ozone column with multifilter UV radiometers. (July 2017) - Piedehierro, A.A.; Cancillo, M.L.; Serrano, A.; Antón, M.; Vilaplana, J.M.
Abstract: The complete recovery of the ozone layer is expected by mid-century but projections depend on the greenhouse scenario and the possible interaction with other atmospheric constituents. Therefore, enlarging the ground-based measuring network is necessary in order to accurately monitor the foreseeable recovery of the ozone layer in the next decades. Multifilter instruments can be used to complement the networks of Dobson and Brewer spectroradiometers. Total ozone column (TOC) can be retrieved from spectral or narrowband global ultraviolet (UV) measurements by comparing the ratio of two close wavelengths with significantly different ozone cross-sections against ratios simulated using a radiative transfer code. This methodology has been widely applied to multifilter radiometers but some unsolved discrepancies between the analyses of different authors regarding which pair of channels to use still remain, even for studies involving the same instrument. The present work aims to analyze TOC estimations derived using different pairs of wavelengths in the UV range (spectral and weighted by the filter response) as it would be recorded by the two main families of multifilter instruments (NILU-UV and GUV). Their spectral responses have been used for determining the response-weighted quantities from Brewer spectra. Validation against TOC values retrieved from direct solar measurements by a reference Brewer spectroradiometer shows that 340:305 wavelengths/channels result in the most accurate TOC estimations. According to our results, TOC values retrieved using response-weighted irradiance are more robust than those obtained using spectral irradiances at certain nominal wavelengths. This finding suggests calibrating multifilter radiometers towards the accurate measurement of response-weighted irradiances, being necessary to characterize the spectral response of each channel. Highlights: Stamnes's method is used for estimating TOC from global UV irradiances. Performance of different UV pairs of spectral and weighted irradiances is analyzed. Best estimations retrieved from 340:305 pair for spectral and weighted irradiances.